Highlighting the cathodic contribution of an electrooxidation pretreatment study on waste activated sludge disintegration - Sari Erkan, Hanife; Bakaraki Turan, Nouha; Onkal Engin, Guleda (WILEY, 2021)
In this study, the effect of the cathodic contribution in the performance of electro-oxidation (EO) pretreatment of waste activated sludge (WAS) was investigated using different electrode pairs, namely titanium dioxide (TiO2)/TiO2, TiO2/TiO2 coated Platine (Pt) and TiO2/TiO2 coated ruthenium dioxide (RuO2) and main operational parameters such as dosage of electrolyte solution (Na2SO4), initial pH, applied current, and electrolysis time were optimized. Disintegration degree (DD) in terms of soluble chemical oxygen demand (CODs) increased with an increase in initial pH of WAS, applied current, and electrolysis time for all pairs of electrodes. Under the optimized conditions (5 g/L Na2SO4, pH 10, 3 A of current, and 100 min of e time), a maximum DD value of 23.93 and 14.26% was obtained using TiO2/RuO2 and Pt/TiO2 electrodes, respectively. However, lower DDCOD value of 12.85% was obtained for TiO2/TiO2 electrodes at similar conditions except for 4 A current. Soluble extracellular polymeric substances analysis and their protein and polysaccharide concentrations confirmed the disintegration of WAS flocs by the EO process. The operational cost (OC) of applied processes was also calculated and OC values were found in the following order: TiO2/RuO2 (46.54 euro/m(3)) > TiO2/TiO2 (41.77 euro/m(3)) > TiO2/Pt (32.99.54 euro/m(3)) from the point of energy consumption.
Keywords: disintegration; electro‐ oxidation; one factor at a time optimization; titanium dioxide electrode; waste sludge; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology